2021
DOI: 10.3390/children8090724
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Levels and Educational Experiences among Dental Graduates in Saudi Arabia Regarding Child Abuse and Neglect: A National Study

Abstract: Background: Child abuse and neglect (CAN) is considered a serious problem worldwide. Dentists have a significant role in recognizing and reporting CAN cases. Aim: The aim of this study was to assess the CAN-related knowledge and educational experiences among Saudi dental graduates. Design: Self-administered questionnaires were distributed to dental graduates from all dental schools in Saudi Arabia (n = 1552). Bivariate and multivariate logistic regression analyses were performed to assess the associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…In a study conducted by Sulimany et al, 60% of dental students from Saudia Arabia had inadequate knowledge of child abuse and neglect and were not satisfied with child abuse and neglect education they received in dental schools [19]. In our study, 39.88% of students had poor knowledge of recognizing signs of child physical abuse; however, 69.80% of students believed they could re-identify abuse.…”
Section: Discussioncontrasting
confidence: 62%
“…In a study conducted by Sulimany et al, 60% of dental students from Saudia Arabia had inadequate knowledge of child abuse and neglect and were not satisfied with child abuse and neglect education they received in dental schools [19]. In our study, 39.88% of students had poor knowledge of recognizing signs of child physical abuse; however, 69.80% of students believed they could re-identify abuse.…”
Section: Discussioncontrasting
confidence: 62%
“…The fear of consequences emerged as a predominant barrier (medical = 82.4%; dental = 68.5%) for not reporting suspected cases of CAN. Sulimany et al (2021) [ 7 ] conducted a national study to assess knowledge levels and educational experiences among dental graduates regarding child abuse and neglect. The study revealed that around 60% of participants had inadequate knowledge regarding CAN.…”
Section: Reviewmentioning
confidence: 99%
“…However, a caveat emerges from the study by Sulimany et al [ 7 ], which points to a significant gap in the knowledge of dental graduates regarding CAN. This divergence highlights the need for a more uniform and comprehensive approach to CAN education across medical and dental curricula, ensuring that future practitioners are adequately equipped to address this critical issue.…”
Section: Reviewmentioning
confidence: 99%
“…It is also critical to promote understanding of the condition by providing in-service training at the facilities where they work [ 12 ]. In the study by Sulimany et al, it was found that only 39.5% of the 988 dental graduates who participated in the evaluation of knowledge levels and educational experiences for CAN felt confident in their capability to recognize a CAN in the case, and only 9.7% were aware of the procedures for reporting such incidents [ 13 ]. Additionally, a fraction of cases could be inadequately addressed due to underreporting by physicians, attributed to factors including, though not confined to, taking into account families’ statements and a lack of familiarity with referral protocols [ 14 ].…”
Section: Introductionmentioning
confidence: 99%